The case for contextualism : knowledge, skepticism, and context. Vol. 1 - DeRose, Keith, 1962- (Oxford : Oxford University Press, 2009)
Contextualism has been hotly debated in recent epistemology & philosophy of language. 'The Case for Contextualism' is a state-of-the-art exposition & defense of the contextualist position, presenting & advancing the most powerful arguments in favor of the view & responding to the most pressing objections facing it.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Contextualism (Philosophy)